Penerapan Pasal 47 Undang-Undang Nomor 34 Tahun 2004 tentang Tentara Nasional Indonesia terkait Penempatan Militer Aktif ke Lembaga Negara didasarkan Asas Kepastian Hukum dan Asas-Asas Umum Pemerintah yang Baik (AUPB) - Kevin Yudha Pratama; Demson Tiopan (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Article 47 of Law Number 34 of 2004 concerning the Indonesian National Army limits the placement of active soldiers in civilian positions, except in certain institutions. However, in practice there are cases of active military deployment that raise legal debates related to the principle of legal certainty and the General Principles of Good Governance (AUPB) such as the principle of legality, the principle of professionalism, the principle of accountability, and the principle of proportionality. This raises questions about the consistency of the application of regulations in governance. This research uses the normative juridical method by examining laws and regulations, legal documents, and case studies related to the implementation of Article 47 of Law Number 34 Year 2004. In addition, this research examines the suitability of practices in the field with the principles of legal certainty and AUPB. The results are expected to identify potential regulatory discrepancies and provide an overview of the application of this regulation in practice. The conclusion of this research emphasizes the importance of upholding legal certainty in the placement of active military in state institutions, in order to maintain the principles of the rule of law and civilian supremacy. The recommendations provided lead to strengthening regulations and supervision so that the implementation of Article 47 of Law Number 34 of 2004 remains in accordance with the principles of good governance.